Health needs of patients with permanent colostomy in North China: A longitudinal qualitative study based on the “Timing It Right” framework - Liu, Baoyu; Wang, Liyan; Li, Qingqing; Pang, Xiaoli (Belitung Nursing Journal, 2026)
Background: Colostomy surgery is the most common method used for the radical treatment and prolongation of life in patients with intestinal diseases. However, patients who undergo a colostomy face various physiological, psychological, and social challenges after the procedure. This necessitates that nurses deliver targeted care tailored to the specific needs of different stages and individual patients. Objective: This study aimed to understand the experiences of health needs of patients with colostomy in order to effectively improve their quality of life across different phases. Methods: A longitudinal qualitative study was conducted. Data were collected between July 2022 and March 2023. A total of 15 patients with permanent colostomy were selected to participate in unstructured interviews, guided by the “Timing It Right” framework. Data analysis was conducted using NVivo 12 software following Colaizzi’s methods. Results: The findings were organized according to the five distinct phases of the “Timing It Right” framework. Three key themes were revealed from the analysis: (1) Meeting physiological needs is the basis for patients with colostomy to recover; (2) Satisfying psychological needs is a necessary condition for improving the quality of life of patients with colostomy; (3) Social adaptation needs are effective ways to improve the quality of life of patients with colostomy. Conclusions: Based on the “Timing It Right” framework, the health status and needs of patients with colostomy differ across the following phases: diagnosis period, perioperative period, discharge preparation period, adjustment period, and adaptation period. This study not only provides a preliminary conceptual model for in-depth investigation of these patients’ health needs at each phase but also offers directional guidance for the future development of phase-specific, patient-centered nursing intervention strategies to better address their dynamic health demands.